Evaluation of Predictive Values of Naples Prognostic Score in Patients with Unresectable Stage III Non-Small Cell Lung Cancer - Guo D; Liu J; Li Y; Li C; Liu Q; Ji S; Zhu S (Dove Medical Press, 2021)
Dong Guo,1 Jiafeng Liu,2 Yanping Li,3 Chao Li,3 Quan Liu,3 Shengjun Ji,4 Shuchai Zhu1 1Department of Radiation Oncology, Fourth Hospital of Hebei Medical University, Shijiazhuang, People's Republic of China; 2Department of Radiotherapy, Rizhao Center Hospital, Rizhao, People's Republic of China; 3Sunshine Union Hospital, Weifang, People's Republic of China; 4Department of Radiotherapy & Oncology, The Affiliated Suzhou Hospital of Nanjing Medical University, Suzhou, People's Republic of ChinaCorrespondence: Shengjun Ji; Shuchai Zhu Email drshengjunji@163.com; 3562069484@qq.comBackground: Naples prognosis score (NPS) is a new prognostic score according to host inflammatory and nutritional state, and it could be useful for predicting tumor prognosis based on albumin level, total cholesterol level, neutrophil-to-lymphocyte ratio, and lymphocyte-to-monocyte ratio. This study aimed to evaluate the clinical significance of Naples prognostic score (NPS) in stage III non-small cell lung cancer patients (NSCLC).Patients and Methods: In this study, 206 patients diagnosed with locally advanced NCCLC receiving chemoradiotherapy were retrospectively reviewed from January 2013 to January 2017. The included patients were divided into 3 groups according to NPS (group 0, group 1, and group 2), and the associations of the NPS with clinical characteristics and outcomes were evaluated among the groups. Survival curves for the NPS were analyzed using the Kaplan-Meier method. Univariate and multivariate analyses were performed using the Cox proportional hazards regression model to evaluate the prognostic value of overall survival (OS) and progression-free survival (PFS).Results: The median follow-up time of this study was 37.0 (range, 13- 59) months. The median OS was 27 months in group 0, 23 months in group 1, and 21 months in group 2, and median PFS was 15, 12 and 13 in group 0, group 1 and group 2, respectively. Age was significantly different among the 3 groups. The NPS was superior to other host inflammatory and nutritional indexes for prognostic risk stratification. In the multivariate analysis, NPS was identified as an independent prognostic indicator for OS and PFS (all P< 0.05).Conclusion: The NPS system is considered to be a useful predictor of outcomes in patients with stage III NSCLC.Keywords: Naples prognostic score, stage III NSCLC, predictive values